Electroencephalographic response to transcranial magnetic stimulation in children: evidence for giant inhibitory potentials - Bender, Stephan; Baßeler, Kristine; Sebastián von Reusner, Imke-Maria; Resch, Franz; Kammer, Thomas; Oelkers-Ax, Rieke; Weisbrod, Matthias (Annals of neurology, 2005)
The electroencephalographic response to transcranial magnetic stimulation (TMS) recently has been established as a direct parameter of motor cortex excitability. Its N100 component was suggested to reflect an inhibitory response. We investigated influences of cerebral maturation on TMS-evoked N100 in 6- to 10-year-old healthy children. We used a forewarned reaction time (contingent negative variation) task to test the effects of response preparation and sensory attention on N100 amplitude. Single-pulse TMS of motor cortex at 105% motor threshold intensity evoked N100 amplitudes of more than 100μV in resting children (visible in single trials), which correlated negatively with age and positively with absolute stimulation intensity. During late contingent negative variation, which involves preactivation of the cortical structures necessary for a fast response, N100 amplitude was significantly reduced. We conclude that (1) N100 amplitude reduction during late contingent negative variation provides further evidence that TMS-evoked N100 reflects inhibitory processes, (2) response preparation and attention modulate N100, and (3) TMS-evoked N100 undergoes maturational changes and could serve to test cortical integrity and inhibitory function in children. Parallels between the inhibitory N100 after TMS (provoking massive synchronous excitation) and the inhibitory wave component of epileptic spike wave complexes are suggested. Ann Neurol 2005
Gesehen am 16.12.2021